2015
DOI: 10.1016/j.eurpsy.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on Tourette Syndrome Beyond Adolescence

Abstract: Although boys are disproportionately affected by tics in Tourette syndrome (TS), this gender bias is attenuated in adulthood and a recent study has suggested that women may experience greater functional interference from tics than men. The authors assessed the gender distribution of adults in a tertiary University-based TS clinic population and the relative influence of gender and other variables on adult tic severity (YGTSS score) and psychosocial functioning (GAF score). We also determined retrospectively th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 47 publications
3
33
0
Order By: Relevance
“…Additionally, our child and adult samples differed with respect to sex; the children included more boys than girls, while the adults were more balanced. This difference reflects epidemiological data, as the sex imbalance (4:1 male:female) reported in childhood TS is attenuated in adulthood TS (71). Nevertheless, examination of the misclassified individuals demonstrated that poor generalizability across age groups was not driven by these factors.…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, our child and adult samples differed with respect to sex; the children included more boys than girls, while the adults were more balanced. This difference reflects epidemiological data, as the sex imbalance (4:1 male:female) reported in childhood TS is attenuated in adulthood TS (71). Nevertheless, examination of the misclassified individuals demonstrated that poor generalizability across age groups was not driven by these factors.…”
Section: Discussionmentioning
confidence: 63%
“…They also found that after adolescence, overall TS impairment was more likely to improve in males and worsen in females. Women had higher Yale Global Tic Severity Scale motor tic scores in adulthood than men and showed greater overall TS‐related impairment . Lewin and colleagues performed a phenomenological characterization of tic disorders in 185 women using a nationwide U.S. Internet sample.…”
Section: Discussionmentioning
confidence: 99%
“…Tics occur in bouts, typically many times in a single day, and are the most common form of movement disorder in children. In child populations with TS the ratio of males to females is estimated at 5.2 to 1, but in adult samples this gender split is closer to parity [2]. Motor tics can be simple or complex in appearance, ranging from repetitive movements to coordinated action sequences.…”
Section: What Is Tourette Syndrome and What Are Tics?mentioning
confidence: 97%